Traumatic abdominal wall hernia repair: an experience in remote hospital of Karnali Academy of Health Sciences Teaching Hospital - Menyangbo, S; Devkota, H; Neupane, M (Journal of Karnali Academy of Health Sciences, 2018)
Not available.